2020
DOI: 10.1111/bcp.14175
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine intake increases performance in the 15‐s Wingate test during the menstrual cycle

Abstract: Aims In male athletes, caffeine is considered an ergogenic aid to increase anaerobic performance during the Wingate anaerobic test (WANT). However, information about the effect of caffeine on WANT performance in female athletes is contradictory. Furthermore, it is unknown whether the ergogenicity of caffeine is present during all the phases of the menstrual cycle. The aim of this study was to investigate the effects of caffeine intake on WANT performance during 3 phases of the menstrual cycle. Methods Thirteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 35 publications
1
57
2
Order By: Relevance
“…Interestingly, Duncan et al (2019) observed a reduction of RPE during Wingate test for the upper-body, but not for the lower-body segment, suggesting that caffeine's effect on RPE depends on body segment exercised (60). Despite the absence of caffeine effect on RPE during lower-body Wingate test observed in some studies (60)(61)(62), our ndings reveal that this bene t can be acquired with caffeine supplementation in this condition. We note that lower RPE identi ed in CAF6 protocol was accompanied by high peak power and mean power, which reinforce the psychostimulant effect of caffeine.…”
Section: Discussioncontrasting
confidence: 51%
“…Interestingly, Duncan et al (2019) observed a reduction of RPE during Wingate test for the upper-body, but not for the lower-body segment, suggesting that caffeine's effect on RPE depends on body segment exercised (60). Despite the absence of caffeine effect on RPE during lower-body Wingate test observed in some studies (60)(61)(62), our ndings reveal that this bene t can be acquired with caffeine supplementation in this condition. We note that lower RPE identi ed in CAF6 protocol was accompanied by high peak power and mean power, which reinforce the psychostimulant effect of caffeine.…”
Section: Discussioncontrasting
confidence: 51%
“…Interestingly, Duncan et al (2019) observed a reduction of RPE during Wingate test for the upper-body, but not for the lower-body segment, suggesting that caffeine's effect on RPE depends on body segment exercised [58]. Despite the absence of caffeine effect on RPE during lower-body Wingate test observed in some studies [58][59][60], our findings reveal that this benefit can be acquired with caffeine supplementation in this condition. We note that lower RPE identified in CAF6 protocol was accompanied by high peak power and mean power, which reinforce the psychostimulant effect of caffeine.…”
Section: Discussioncontrasting
confidence: 51%
“…Ten women participants were tested during the follicular phase of their menstrual cycle and five were tested during the luteal phase according to a mobile application (Mycalendar ® , Period-tracker, USA). However, recent investigations indicate that the effect of caffeine on exercise performance is similar across all phases of the menstrual cycle [ 43 , 44 ]. All participants were considered as low caffeine consumers (60 ± 25 mg·d −1 or 0.76 mg·kg −1 ·d −1 ([ 45 ])) measured with a valid semi-quantitative caffeine intake questionnaire [ 46 ].…”
Section: Methodsmentioning
confidence: 99%